Increased circulating progranulin is not sufficient to induce cardiac dysfunction or supraventricular arrhythmia - McElhanon, Kevin E.; Huff, Tyler C.; Hirenallur-Shanthappa, Dinesh; Miller, Russell A.; Christoforou, Nicolas (Scientific reports, 2023)
Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia, and the incidence of new-onset AF has been increasing over the past two decades. Several factors contribute to the risk of developing AF including age, preexisting cardiovascular disease, chronic kidney disease, and obesity. Concurrent with the rise in AF, obesity has followed the same two-decade trend. The contribution of circulating proteins to obesity-related AF is of particular interest in the field. In this study, we investigated the effects of increased circulating levels of the glycoprotein progranulin on the development of supraventricular arrhythmias and changes to cardiac function. AAV8-mediated overexpression of full-length mouse progranulin was used to increase plasma protein levels and determine susceptibility to supraventricular arrhythmias and changes in cardiac structure and function. C57Bl/6N mice were subjected to increased circulating levels of progranulin for 20 weeks. Cardiac conduction was evaluated by surface ECG with and without isoproterenol challenge, and cardiac structure and function were measured by echocardiography after 20 weeks of circulating progranulin overexpression. Increased circulating levels of progranulin were maintained throughout the 20-week study. The cardiac structure and function remained unchanged in mice with increased circulating progranulin. ECG indices (P wave duration, P amplitude, QRS interval) were unaffected by increased progranulin levels and no arrhythmogenic events were observed following the isoproterenol challenge. In our model, increased levels of circulating progranulin were not sufficient to induce changes in cardiac structure and function or elicit ECG abnormalities suggestive of susceptibility to supraventricular arrhythmias.